Digestive Enzyme Activities in Barred Loach (Nemacheilus fasciatus, Val., 1846.): Effect of pH and Temperature - Untung Susilo; Farida Nur Rachmawati; Eko Setio Wibowo; Ristiandani R. Pradhyaningrum; Koni Okthalina; Muthiara N. A. Mulyani (Universitas Jenderal Soedirman, 2022)
This study aims to determine the total protease, lipase, and amylase activities at different pHs, as well as pepsin and trypsin-like at different temperatures. A total of 240 individuals have been used in this study. Enzyme activity was measured by the spectrophotometer method. The effect of pH was evaluated on protease, lipase, and amylase activity, while the effect of temperature was evaluated on pepsin and trypsin-like activities.The results showed that the total protease activity at pH 7.0-10.0 was significantly higher than pH 1.7-5.0 (P <0.05). Furthermore, the activity of lipase was significantly higher at pH 5.0-7.0 than pH 1.7, 3.4, and 10.0. Also, the activity of amylase at pH 7.0-8.0 was significantly higher (p <0.05) than pH 1.7-5.0 and pH 10.0. Moreover, the pepsin-like activity in the anterior gut was significantly higher (p <0.05) than the posterior gut.Conversely, trypsin-like activity in the posterior gut was significantly higher (p <.05) than the anterior gut. Additionally, the pepsin-like activity was significantly higher at 45°C compared to different temperatures (p <0.05), whereas trypsin-like was significantly (p <0.05) higher at 60 °C than othertemperatures. Conclusively, the total protease and amylase activity was higher under neutral to slightly alkaline conditions, while lipase was higher under acidic to neutral conditions. Furthermore, the pepsin-like activity was only found in the anterior gut, whereas trypsin-like was higher in the posterior gut. The optimal temperature for pepsin-like and trypsin-like activity was 45 °C and 60 °C, respectively.